2021
DOI: 10.1093/mnras/stab3075
|View full text |Cite
|
Sign up to set email alerts
|

Rescued from oblivion: detailed analysis of archival Spitzer data of SN 1993J

Abstract: We present an extensive analysis of the late-time mid-infrared (mid-IR) evolution of the Type IIb SN 1993J from 10–26 yr post-explosion based on archival – mostly previously unpublished – photometric data from the Spitzer Space Telescope in conjunction with an archival InfraRed Spectrograph spectrum. SN 1993J is one of the best-studied supernovae (SNe) with an extensive decade-long multiwavelength data set published in various papers; however, its detailed late-time mid-IR analysis is still missing from the li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…The asymmetries in the broad oxygen lines in the late-time spectra led Fransson et al [42] and Milisavljevic et al [76] to speculate on the presence of dust in the SN, and modelling by B17 of the redblue asymmetries in the latter's day 6101 spectrum using DAMOCLES yielded an ejecta silicate dust mass of ∼0.1 M . Zsíros et al [137] modelled archival 3.6-24-µm Spitzer SEDs of SN 1993J, obtained between 3875 and 5359 days postexplosion, and found there could be either ∼ 5 × 10 −3 M of silicate dust or ∼ 1 × 10 −3 M of amorphous carbon dust, emitting at T∼200 K, significantly less than the ∼0.1 M found by B17, which we attribute to the insensitivity of the Spitzer measurements to colder dust emitting longwards of 24 µm.…”
Section: Sn 1993jmentioning
confidence: 99%
“…The asymmetries in the broad oxygen lines in the late-time spectra led Fransson et al [42] and Milisavljevic et al [76] to speculate on the presence of dust in the SN, and modelling by B17 of the redblue asymmetries in the latter's day 6101 spectrum using DAMOCLES yielded an ejecta silicate dust mass of ∼0.1 M . Zsíros et al [137] modelled archival 3.6-24-µm Spitzer SEDs of SN 1993J, obtained between 3875 and 5359 days postexplosion, and found there could be either ∼ 5 × 10 −3 M of silicate dust or ∼ 1 × 10 −3 M of amorphous carbon dust, emitting at T∼200 K, significantly less than the ∼0.1 M found by B17, which we attribute to the insensitivity of the Spitzer measurements to colder dust emitting longwards of 24 µm.…”
Section: Sn 1993jmentioning
confidence: 99%
“…More recently, mid-IR imaging of SN 1980K over 40 yr after explosion by Zsíros et al (2023) reported its dust mass M d ≈ 0.02M e . However, the SED analysis indicates a much greater amount of dust (∼0.24-0.58M e ), suggesting a dust mass fraction of η d  0.20.…”
Section: Observational Constraints On Large Dust Masses Of Snementioning
confidence: 99%
“…In addition, over the past decade, there has been much discussion of the indeterminacy of the 26 Al yield based on a more modern understanding of stellar evolution and SN explosions (e.g., Woosley & Heger 2007;Tur et al 2010;Brinkman et al 2019Brinkman et al , 2021Brinkman et al , 2023. Observations of dust mass abundance ratios, also important in this study, are now available for SNe with younger timescales of interest in this study (∼40 yr;e.g., SN 1987A andSN 1980K;Matsuura et al 2011;Zsíros et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Chevalier & Fransson 1994;Woosley et al 1994;Nakar & Piro 2014, and references) and it has been studied for many years and in different wavelengths (in radio, e.g. Marcaide et al 2009;Martí-Vidal et al 2011; and most recently published in IR by Zsíros et al 2022). Among the few SNe of type Ib included in the list, we aim to dedicate more attention to SN2008D (in Section 4.2).…”
Section: Published Double-peaked Snementioning
confidence: 99%